2011
DOI: 10.1186/1755-1536-4-23
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine (C-C motif) ligand 2 mediates direct and indirect fibrotic responses in human and murine cultured fibrocytes

Abstract: BackgroundFibrocytes are a population of circulating bone-marrow-derived cells that express surface markers for leukocytes and mesenchymal cells, and are capable of differentiating into myofibroblasts. They have been observed at sites of active fibrosis and increased circulating numbers correlate with mortality in idiopathic pulmonary fibrosis (IPF). Inhibition of chemokine (C-C motif) receptor 2 (CCR2) during experimental models of lung fibrosis reduces lung collagen deposition, as well as reducing lung fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 36 publications
(74 reference statements)
5
47
0
Order By: Relevance
“…Patients with IPF have elevated numbers of fibrocytes in circulation, and increased percentages of fibrocytes predict early mortality (23). Our studies demonstrated that CCL12 recruited fibrocytes in mice via CCR2 (6) and that CCR2 stimulation of fibrocytes increased expression of collagen 1 (5); these findings were confirmed in human studies (24). Taken together, our data show that CCR2-binding chemokines recruit a novel profibrotic cell type and play important roles in cellular activation and differentiation.…”
Section: Ccr2-binding Chemokines and Lung Fibrosis: More Than Just MIsupporting
confidence: 78%
“…Patients with IPF have elevated numbers of fibrocytes in circulation, and increased percentages of fibrocytes predict early mortality (23). Our studies demonstrated that CCL12 recruited fibrocytes in mice via CCR2 (6) and that CCR2 stimulation of fibrocytes increased expression of collagen 1 (5); these findings were confirmed in human studies (24). Taken together, our data show that CCR2-binding chemokines recruit a novel profibrotic cell type and play important roles in cellular activation and differentiation.…”
Section: Ccr2-binding Chemokines and Lung Fibrosis: More Than Just MIsupporting
confidence: 78%
“…Consistent with the reported secretory profile of fibrocytes [4], many of these monocyte/macrophage lineage cells also showed high expression levels of growth factors, such as TGF-β1, MCP-1 (Ccl2), and vascular endothelial growth factor (VEGF). Moreover, these cells also expressed receptors for growth factors, such as receptors for SDF-1α (Cxcr4), MCP-1 (Ccr2), and TGF-β1 (Tgfr1), similar to traditionally defined fibrocytes [30,31]. …”
Section: Resultsmentioning
confidence: 99%
“…Eker et al 35 reported that human fibrocytes express functional CCR2, after using an optimized technique for isolation of fibrocytes from human blood and demonstrating expression of functional CCR2 by a subpopulation of these cells. Signaling through ligand-CCR2 interactions induces the proliferation of human blood fibrocytes, differentiation of fibrocytes into myofibroblasts, production of type I collagen, and a chemotactic response.…”
Section: Discussionmentioning
confidence: 99%